ManajemenPerencanaan Pembangunan Daerah Berbasis Penelitian & Pengembangan Dan Desain & Inovasi - Herie Saksono (Badan Riset dan Inovasi Daerah Provinsi Kalimantan Selatan, 2019)
Development management should be able to optimize development capital in an area and manage it to realize better welfare. Unfortunately, not all development stakeholders have the understanding and ability to manage development capital in their region. In general, management of regional development planning is still conventional and has not made the results of research, development, design, and innovation as a reference. This condition certainly becomes very contrasting when faced with the digital era as the impact of the rapid advancement of science and technology accompanied by the dominance of millennia with its high curiosity and prioritizes research, development, design, and innovation as its work and performance. What is the ideal form of regional development management? This study uses a qualitative approach with descriptive analysis. The aim is to be able to describe the importance of managing development capital based on research, development, design, and innovation. There are seven (7) aspects analyzed from all regencies/cities in the administrative region of Southeast Sulawesi Province. Through the results of the analysis it was concluded that it was important for each district / city government to manage planning and development in the region based on research, development, design, and innovation (research-based planning & research-based development). It is recommended that regional governments prioritize planning mechanisms that refer to the results of research, development, design, and innovation in building their regions. Thus, it is hoped that it can improve the performance of regional government administration and the community will increasingly feel the benefits. Abstrak Manajemen pembangunan semestinya mampu mengoptimalkan modal pembangunan di suatu wilayah dan mengelolanya untuk mewujudkan kesejahteraan yang lebih baik. Akan tetapi belum seluruh pemangku kepentingan pembangunan memiliki pemahaman dan berkemampuan mengelola modal pembangunan di wilayahnya. Pada umumnya, pengelolaan perencanaan pembangunan daerah masih bersifat konvensional dan belum menjadikan hasil penelitian, pengembangan, desain, dan inovasi sebagai acuannya. Melalui studi ini diharapkan diperoleh model ideal pengelolaan pembangunan daerah. Studi ini menggunakan pendekatan kualitatif dengan analisis deskriptif. Terdapat tujuh (7) aspek yang dianalisis dari seluruh kabupaten/kota di wilayah administrasi pemerintahan Provinsi Sulawesi Tenggara. Berdasarkan hasil analisis disimpulkan bahwa penting bagi setiap pemerintah daerah kabupaten/kota untuk mengelola perencanaan dan pembangunan di daerahnya berbasis penelitian, pengembangan, desain, dan inovasi (research-based planning & research-based development). Direkomendasikan agar pemerintah daerah mengedepankan mekanisme perencanaan yang mengacu kepada hasil penelitian, pengembangan, desain, dan inovasi dalam membangun daerahnya. Dengan demikian, diharapkan dapat meningkatkan kinerja penyelenggaraan pemerintahaan daerah dan masyarakat semakin merasakan manfaatnya.